Work here now : think like a human and build a powerhouse workplace - Swift, Melissa (John Wiley & Sons, Inc., 2023)
". The book takes its title from a simple insight: we would never run a machine at such a pace, duration, and rhythm such that it broke all of the time?so why do we do exact that to our human workers? The reality is, this model doesn?t work for anyone. Organizations have dumped millions into consulting from folks like myself, with incremental results; workers have raged from picket lines to Reddit with stop-and-start progress at best. By assuming the interests of these two groups are not at cross purposes ? and being willing to aim the analytical laser in some unexpected places ? You Wouldn?t Run a Machine This Way provides a roadmap to better work that generates wins for organizations and employees alike. You Wouldn?t Run a Machine This Way explores an array of ways we?ve made work downright inhuman - in a way that, ironically, actually stifles the growth and profitability of organizations. Foundational practices we take for granted ? for instance, trying to improve the performance of the individual human being - actually produce worse results than doing nothing at all. And, similar to the old joke about teaching a pig to dance being both a waste of your time and an annoyance for the pig, these efforts both waste corporate money and time and ? critically - drive human workers to exhaustion, burnout, and even death. To build a better model of work, You Wouldn?t Run a Machine This Way argues, we have to look in some unexpected places. Your people strategy? It?s being built by geopolitics and local jurisprudence, not your HR team; immigration, migration, and incarceration have a seismic impact on workforces that companies serially underestimate"--